Increased circulating cell‐free DNA levels and mtDNA fragments in interventional cardiologists occupationally exposed to low levels of ionizing radiation. (18th October 2014) - Borghini, Andrea; Mercuri, Antonella; Turchi, Stefano; Chiesa, Maria Rosa; Piccaluga, Emanuela; Andreassi, Maria Grazia
Abstract : Circulating cell‐free DNA (ccf‐DNA) and mtDNA (ccf‐mtDNA) have often been used as indicators of cell death and tissue damage in acute and chronic disorders, but little is known about changes in ccf‐DNA and ccf‐mtDNA concentrations following radiation exposure. The aim of the study was to investigate the impact of chronic low‐dose radiation exposure on serum ccf‐DNA levels and ccf‐mtDNA fragments (mtDNA‐79 and mtDNA‐230) of interventional cardiologists working in high‐volume cardiac catheterization laboratory to assess their possible role as useful radiation biomarkers. We enrolled 50 interventional cardiologists (26 males; age = 48.4 ± 10 years) and 50 age‐ and gender‐matched unexposed controls (27 males; age = 47.6 ± 8.3 years). Quant‐iT™ dsDNA High‐Sensitivity assay was used to measure circulating ccf‐DNA isolated from serum samples. Quantitative analysis of mtDNA fragments was performed by real‐time PCR. No significant relationships were found between ccf‐DNA and ccf‐mtDNA, and age, gender, smoking, or other clinical parameters. Ccf‐DNA levels (44.2 ± 31.1 vs. 30.6 ± 19.2 ng/ml, P  = 0.013), ccf‐mtDNA‐79 (2.6 ± 2.1 vs. 1.1 ± 0.8, P < 0.01), and ccf‐mtDNA‐230 copies (2.0 ± 1.8 vs. 1.04 ± 0.9, P  = 0.02) were significantly higher in interventional cardiologists compared with the non‐exposed group. In a subset ( n  = 15) of interventional cardiologists with a reliable reconstruction of cumulative professional exposure (59.7 ± 48.4 mSv; range: 1.4–182 mS), ccf‐DNA (53.2 ± 41.3 vs. 36.4 ± 22.9 and 32.2 ± 20.5, P  = 0.08), mtDNA‐79 (2.4 ± 2.1 vs. 2.03 ± 1.7 and 1.09 ± 0.82, P  = 0.05), and mtDNA‐230 (2.0 ± 2.2 vs. 1.5 ± 1.4 and 1.04 ± 0.9, P  = 0.09) tended to be significantly increased in high‐exposure subjects compared with both low‐exposure interventional cardiologists and controls. Our results provide evidence for a possible role of circulating DNA as a relevant biomarker of cellular damage induced by exposure to chronic low‐dose radiation. Environ. Mol. Mutagen. 56:293–300, 2015. © 2014 Wiley Periodicals, Inc.